Porous poly(ethylene glycol)-polyurethane hydrogels as potential biomaterials - Divakaran, Anumon V.; Torris, Arun A. T.; Lele, Ashish K.; Badiger, Manohar V. (Polymer International, 2015)
We report the synthesis of porous poly(ethylene glycol)-polyurethane (PEG-PU) hydrogels using PEG-4000 as a soft segment and 4,4-methylenebis(cyclohexylisocyanate) as a hard segment. The degree of swelling in the hydrogels could be controlled by varying the amount of crosslinking agent, namely 1,2,6-hexanetriol. Structural characterization of the hydrogels was performed using solid-state C-13 NMR and Fourier transform infrared spectroscopy. Wide-angle X-ray diffraction studies revealed the existence of crystalline domains of PEG and small-angle X-ray scattering studies showed the presence of lamellar microstructures. For generating a porous structure in the hydrogels, cryogenic treatment with lyophilization was used. Scanning electron microscopy and three-dimensional micro-computed tomography imaging of the hydrogels indicated the presence of interconnected pores. The mechanical strength of the hydrogels and xerogels was measured using dynamic mechanical analysis. The observed dynamic storage moduli (E) for the equilibrium swollen and dry gels were found to be 0.15 and 4.2 MPa, respectively. Interestingly, the porous PEG-PU xerogel also showed E of 5.6 MPa indicating a similar mechanical strength upon incorporating porosity into the gel matrix. Finally, preliminary cytocompatibility studies showed the ability of cells to proliferate in the hydrogels. These gels show promise for applications as scaffolds and implants in tissue engineering. (c) 2014 Society of Chemical Industry
Keywords: hydrogels; permeability; poly(ethylene glycol); polyurethane; porosity